Islamic concept of Intermediation (Tawassul) - Tahirulqadri, Muhammad, 1951- (Islamic belief series., 2007)
he Prophethood and Messengership of the Holy Prophet(Peac Be Up Him and His Household) continues uninterrupted even after his death. He still exists among us as the Prophet and the Messenger of Allah(Peac Be Up Him and His Household) and this will continue down to the Day of Judgement, untarnished and unsullied. When all the other laws are still valid, why shouldn’t the law of intermediation continue to be valid?